2015
DOI: 10.1186/s12913-015-1227-z
|View full text |Cite
|
Sign up to set email alerts
|

Health professional perspectives on systems failures in transitional care for patients with dementia and their carers: a qualitative descriptive study

Abstract: BackgroundHealthcare professionals engage in discharge planning of people with dementia during hospitalisation, however plans for transitioning the person into community services can be patchy and ineffective. The aim of this study was to report acute, community and residential care health professionals’ (HP) perspectives on the discharge process and transitional care arrangements for people with dementia and their carers.MethodsA qualitative descriptive study design and purposive sampling was used to recruit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 24 publications
2
78
0
5
Order By: Relevance
“…This is similar to the recent National Stroke Audit data that reported, although 75% of stroke survivors needed ongoing rehabilitation, only 46% were referred to rehabilitation services (Stroke Foundation, ). The pressure to discharge patients quickly can mean that they do not receive information from all team members before they are sent home, and this is confirmed by other studies (Kable et al, ; Waring et al, ).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…This is similar to the recent National Stroke Audit data that reported, although 75% of stroke survivors needed ongoing rehabilitation, only 46% were referred to rehabilitation services (Stroke Foundation, ). The pressure to discharge patients quickly can mean that they do not receive information from all team members before they are sent home, and this is confirmed by other studies (Kable et al, ; Waring et al, ).…”
Section: Discussionmentioning
confidence: 60%
“…Discharge summaries should be completed and sent on the day of discharge. Routine provision of home medication reviews after discharge could contribute to reduced medication risk and fewer complications and readmission to hospital (Kable et al, ). Improved carer involvement and support might make it possible for carers to cope better and assist stroke survivors at home to avoid adverse outcomes (Hvalvik & Reierson, ; King et al, ; Naylor & Keating, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in Australia, a study by Kable, Chenoweth, Pond and Hullick (2015) demonstrates that Swedish studies also confirm these findings. For example, Ekdahl, Linderholm, Hellstrom, Andersson & Friedrichsen (2016) suggested that nurses are preoccupied with freeing up beds which led to failing to meet the high needs of elderly patients and this also generated feelings of guilt and frustration in the staff and contributed to making the patients feel unwelcome.…”
Section: Introductionmentioning
confidence: 75%